The Meaning (בַיִת) Of The House In Psalm 127:1 - Sahara Theo (Theological Journal Kerugma, 2023)
The title of this research is the meaning (בַיִת) of the house in Psalm 127:1. "The purpose of this research is to explain the meaning of the phrase "house/baby" as a building structure and as a family in Psalm 127:1. The author uses exegesis studies, in grammatical studies, semantic studies and interpretations related to Biblical Counseling. There are two meanings as a conclusion in this study: first, the house is defined as a building structure (the temple, David's palace, building), and second, the house is a family, a household. Psalm 127 warns that every building of home and family involves and relies on God.